ОСНОВНІ ПІДХОДИ ДО ВИВЧЕННЯ СТИЛІСТИКИ УКРАЇНСЬКОЇ МОВИ В НАВЧАЛЬНИХ ВИДАННЯХ ДЛЯ ВИЩОЇ ШКОЛИ (РЕТРОСПЕКТИВА І СЬОГОДЕННЯ) - Попович, Анжеліка (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглядаються основні підходи до вивчення стилістики української мови як навчальної дисципліни в підручниках і навчальних посібниках для студентів вищих навчальних закладів. Виокремлюються тропеїчно-фігуральний, мовно-рівневий, функційно-стильовий і комунікативно-прагматичний підходи. Аналізові піддаються навчальні видання зі стилістики, опубліковані від початку ХХ століття дотепер (Н. Бабич, І. Білодід, Л. Булаховський, В. Ващенко, Г. Волкотруб, В. Домбровський, П. Дудик, М. Зарицький, А. Коваль, О. Курило, К. Лучаковський, Л. Мацько, О. Пономарів, О. Потебня, В. Сімович, С. Смеречинський, О. Синявський, М. Сулима, Б. Ткаченко, І. Франко, І. Чередниченко та інші). В статье рассматриваются основные подходы к изучению стилистики украинского языка как учебной дисциплины в учебниках и учебных пособиях для студентов высших учебных заведений. Выделяются тропеично-фигуральный, языково-уровневый, функционально-стилевой и комуникативно-прагматический подходы. Анализ осуществляется на учебных изданиях, изданных от начала ХХ века до наших дней (Н. Бабич, И. Билодид, Л. Булаховский, В. Ващенко, Г. Волкотруб, В. Домбровский, П. Дудик, Н. Зарицкий, А. Коваль, Е. Курило, К. Лучаковский, Л. Мацько, А. Пономарив, А. Потебня, В. Симович, Н. Сулима, А. Синявский, С. Смеречинский, Б. Ткаченко, И. Франко, И. Чередниченко и другие). The questions about methods of teaching stylistics as the educational discipline in high school are very topical. In the article the approaches to studying the stylistics of Ukrainian language in educational textbooks for university students are explained. The trope-and-figurative, linguistic level, functional-and-stylistic and communicative-and-pragmatic approaches are distinguished. The analysis of educational editions in stylistics, which have been published since the early twentieth century until now, is made (I. Franko, O. Potebnia, K. Luchakovskyi, V. Dombrovskyi, B. Tkachenko, L. Bulakhovskyi, V. Simovych, O. Kurylo, M. Sulyma, O. Syniavskyi, S. Smerechynskyi, I. Bilodid, A. Koval, V. Vaschenko, I. Cherednychenko, M. Zarytskyi, H. Volkotrub, L. Matsko, P. Dudyk, O. Ponomariv and others). The approach of linguistic level was defined as the dominating one. At present stage it is needed to consider the communicative and pragmatic aspects of discipline studying, as there are active processes of interaction of linguostylistics’ categories with philosophy of language, culturology, sociolinguistics, pragmalinguistics, communicative linguistics, literature studies, ethnolinguistics, etc.